50 Years of Forest Management in India - Shah, S. A. (Indian Forester, 1998)
Forest Management during the 50 years ofIndependence has made a full circle: from Conversion to Uniform Crops and back to Conversion to Irregular Crops. The early years of Independence were characterized by production (for industry) euphoria. Von Mon Roy’s Report on the status of raw material supply in the country and the National Commission on Agriculture’s Report reinforced this industry oriented productiono The objective of Sustained Yield of Timber which guided and governed Forest Management during the early 30 years of Independence, could not be achieved. The concept ofaNormal Forest in which each age-class occupies an equal area came under attack for environmental reasons. 1980 was watershed year. The World Conservation Strategy altered the way we look at Forests and Forest Management. During the subsequent years, environmental awareness and consciousness swept the world. The Earth Summit, the Convention on Biological Diversity and the recent Climate Change Convention have all focused on the need to maintain forest cover, conserve biodiversity and ensure sustainability. This led to the stoppage of Clear Cutting System, and the need for increasing production of non-wood products for sustaining forest dependent communities. All this is possible only by making forest sustainable in all its dimensions. The forests of the country are sick and unstable and have suffered heavily in productivity. A little over 30 million ha have been degraded. The restoration of these forests requires a different approach; a different technology and a different administrative structure. This is one of the biggest challenges facing the foresters to-day.